Effect of delayed mating on reproductive performance of Lasioderma serricorne (F.) (Coleoptera: Anobiidae) - Mahroof, Rizana; Amoah, Barbara; Gerken, Alison; Campbell, Jim (Julius-Kühn-Archiv, 2018)
With the ban of methyl bromide and the many problems associated with the use of other synthetic chemicals, current research have focused on non-chemical alternatives and integrated pest management approach for the control of stored product insect pests. Mating disruption is one technique being investigated for its effect on stored product insects. In this study, we determined the effect of age at mating on the reproductive rate and longevity of the cigarette beetle, Lasioderma serricorne (Coleoptera: Anobiidae). We disrupted the mating approach by delaying the insects from mating for different time periods in days. Same age virgin male and female cigarette beetles were paired to mate soon after emergence (0 d old), or delayed from mating for 1–14 d. In another experiment, we maintained the age of the male at 0 d old and varied the age of the female from 0– 14 d old and vice versa. Insects were observed daily for longevity and F1 progeny was recorded 7–10 weeks after mating pairs were put together. Progeny production generally decreased with age of adults at mating. The number of F1 progeny produced by same age adults varied from 10 per female to 59 per female. Similarly, the number of progeny decreased the longer one sex was delayed from mating. Findings from this study may provide information for the development of mating disruption techniques that can delay mating and may be effective in keeping populations of L. serricorne below levels that would warrant a control action.